The relationship of personality dimensions and self-regulation components to the success of Iranian boxers - Khani, M. (Serbian Journal of Sports Sciences, 2011)
Evaluation and identification of the factors which influence athletes´ success is one of the most important issues in their selection, orienting, raising, and supporting. The present study was done with the purpose of assessing the relationship of personality dimensions and self-regulation components to success in boxing. 237 senior amateur boxers (20.6±3.7 years old with 4.8±3.4 years boxing background) participated in this study. NEO-Five Factor Inventory, Boxers´ Success Questionnaire, and Self-Regulation Questionnaire were used in data collection. All questionnaires have acceptable validity and reliability and Cronbach's Alpha coefficients were 0.83, 0.88, and 0.89, respectively, which indicates high internal consistency of these tests. The data were analyzed using a multiple linear regression allowing the simultaneous testing and modeling of multiple independent variables (the stepwise method). The findings showed that personality dimensions except extroversion and agreeableness, and components of self-regulation except self-assessment, have satisfactory correlation with success in boxing. Stepwise regression analysis indicated that two dimensions of Big Five personality factors - neurosis, openness, receiving related information, and searching for different options among self-regulation components can explain the success of boxers. Big Five personality factors and self-regulation components are reliable tools to predict an athlete's success in boxing. In addition, Miller and Brown`s model of self-regulation was admitted in the sport area.